Kohesifitas Sosial Harmoni Umat Beragama Pada Masyarakat Lombok (Pendekatan Sosiologi Agama): (Pendekatan Sosiologi Agama) - Wirata, I Wayan (Jayapangus Press, 2023)
Lombok society is a pluralism society. The people of Lombok are inhabited by tribes, races, religions and civilizations by upholding the values of togetherness, unity and kinship. Harmony and togetherness occur when there is conducive interaction and a sense of belonging to each other by always prioritizing a sense of humanism and kinship. For this reason, it is hoped that dynamic and open interaction and communication will occur, so that they can implement traditional values that have been rooted in their ancestors. The existence of togetherness provides an identity and pattern of society that is conducive, effective, and productive in order to create a sense of togetherness, brotherhood, unity among religious communities. Thus there is a level of cohesiveness and religiosity strengthening the harmonization of religious communities in Lombok which is safe, peaceful and peaceful. The research method uses qualitative data collection techniques through questionnaires, in-depth interviews, and documents. Data analysis used interpretive qualitative analysis. Document analysis was carried out using several documents obtained from the Office of the Ministry of Religion of West Nusa Tenggara Province. Based on the information and data collected, this study found that the cohesiveness of harmony as a reflection of Lombok society is as follows: a) Forms of social cohesiveness of religious harmony in Lombok society through: humanistic communication and interaction to create peace; b) The process of social cohesiveness of religious harmony in the Lombok community through instilling a sense of brotherhood and maintaining a sense of unity and upholding ancestral civilization, and c) The meaning of social cohesiveness of religious harmony in Lombok society has cultural, social and brotherhood meanings.